2007
DOI: 10.17796/jcpd.31.2.tu54hu4231w1073q
|View full text |Cite
|
Sign up to set email alerts
|

Post Expansion Evaluation of the Midpalatal Suture in Children Submitted to Rapid Palatal Expansion: a CT Study

Abstract: The aim of this prospective study was to evaluate the midpalatal suture in children submitted to rapid palatal expansion, at the end of the retention stage, with CT scans. The sample was comprised of 17 children aged between 5 years 2 months and 10 years 5 months. The tomographic images showed that the midpalatal suture was completely ossified from the anterior nasal spine area to the posterior nasal spine area at the end of the retention phase, that is, 8 to 9 months postexpansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 26 publications
3
33
0
3
Order By: Relevance
“…This difference could be due to the different methods of investigation, since, in the study by Podesser et al, 8 postexpansion CT examinations were performed after removing the appliance; this might lead to some immediate rebound. da Silva Filho et al 9 reported expansion values of 2.21 mm at ASW and 0.98 mm at PSW. These values are smaller than the amount of expansion obtained in our study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This difference could be due to the different methods of investigation, since, in the study by Podesser et al, 8 postexpansion CT examinations were performed after removing the appliance; this might lead to some immediate rebound. da Silva Filho et al 9 reported expansion values of 2.21 mm at ASW and 0.98 mm at PSW. These values are smaller than the amount of expansion obtained in our study.…”
Section: Discussionmentioning
confidence: 97%
“…In agreement with previous authors, the midpalatal suture on the coronal images showed a triangular radiolucent area, where the base is turned forward. 6,[8][9][10] The amount of expansion at the anterior portion of the suture (ASW, 3.01 mm) was variable among the subjects (range, 1.82-4.25 mm). Going from the anterior to the middle to the posterior aspect of the suture, only 43%, 31%, and 16% of the expansion of the screw (7 mm) could be explained by the distraction across the suture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 In the available literature cone-beam CT technology is described by several author [45][46][47] as a means to examine RME effects; 48,49 however, the morphological appearance of the suture structure itself or measurements of the width has not been described before.…”
Section: Resultsmentioning
confidence: 99%